Affordable and equitable access to subsidised outpatient medicines? Analysis of co-payments under the Additional Drug Package in Kyrgyzstan - Sabine Vogler; Peter Schneider; Guillaume Dedet; Hanne Bak Pedersen (BMC, 2019)
Abstract Background Out-of-pocket (OOP) payments can constitute a major barrier for affordable and equitable access to essential medicines. Household surveys in Kyrgyzstan pointed to a perceived growth in OOP payments for outpatient medicines, including those covered by the benefits package scheme (the Additional Drug Package, ADP). The study aimed to explore the extent of co-payments for ADP-listed medicines and to explain the reasons for developments. Methods A descriptive statistical analysis was performed on prices and volumes of prescribed ADP-listed medicines dispensed in pharmacies during 2013-2015 (1,041,777 prescriptions claimed, data provided by the Mandatory Health Insurance Fund). Additionally, data on the value and volume of imported medicines in 2013-2015 (obtained from the National Medicines Regulatory Agency) were analysed. Results In 2013-2015, co-payments for medicines dispensed under the ADP grew, on average, by 22.8%. Co-payments for ADP-listed medicines amounted to around 50% of a reimbursed baseline price, but as pharmacy retail prices were not regulated, co-payments tended to be higher in practice. The increase in co-payments coincided with a reduction in the number of prescriptions dispensed (by 14%) and an increase in average amounts reimbursed per prescription in nearly all therapeutic groups (by 22%) in the study period. While the decrease in prescriptions suggests possible underuse, as patients might forego filling prescriptions due to financial restraints, the growth in average amounts reimbursed could be an indication of inefficiencies in public funding. Variation between the regions suggests regional inequity. Devaluation of the national currency was observed, and the value of imported medicines increased by nearly 20%, whereas volumes of imports remained at around the same level in 2013-2015. Thus, patients and public procurers had to pay more for the same amount of medicines. Conclusions The findings suggest an increase in pharmacy retail prices as the major driver for higher co-payments. The national currency devaluation contributed to the price increases, and the absence of medicine price regulation aggravated the effects of the depreciation. It is recommended that Kyrgyzstan should introduce medicine price regulation and exemptions for low-income people from co-payments to ensure a more affordable and equitable access to medicines.